2017
DOI: 10.22159/ajpcr.2017.v10i3.16417
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Metronidazole Microspheres-Loaded Bioadhesive Vaginal Gel

Abstract: Objectives: The objective of the present work is to develop and characterize metronidazole microsphere-loaded bioadhesive vaginal gel to ensurelonger residence time at the infection site, providing a favorable release profile for the drug.Methods: Microsphere was prepared by solvent evaporation method in various ratios of metronidazole to poly-ε-caprolactone (PCL). Physicochemicalevaluation of microspheres includes determination of solubility in simulated vaginal fluid, partition coefficient (n-octanol/citrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The results in This was in a great accordance with Kalita et al who found that metronidazole entrapment increased with an increase in HPMC K4 M concentration [4].…”
Section: Entrapment Efficiencysupporting
confidence: 91%
See 1 more Smart Citation
“…The results in This was in a great accordance with Kalita et al who found that metronidazole entrapment increased with an increase in HPMC K4 M concentration [4].…”
Section: Entrapment Efficiencysupporting
confidence: 91%
“…Hani et al formulated clotrimazole into intravaginal microspheres by the spray drying technique, which was inserted into a mucoadhesive gel for the local treatment of vaginal candidiasis [3]. Kalita et al increased the vaginal residence time of metronidazole through the preparation of PLC microspheres, which were incorporated into carbopol 934p and HPMC K4 M bioadhesive gel [4]. Khan and Thakur developed novel chitosan mucoadhesive microspheres for vaginal administration of tenofovir disproxil fumarate [5].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in SA concentration led to an increase in the number of cross-linking points, so more drug would be entrapped and eventually a significant reduction in the total drug release from the resulting beads [39]. This could also be attributed to the formation of gelatinous mass on the surface of the formed beads on contact with the dissolution medium which hindered further penetration of the dissolution medium and increased the diffusional pass length [3,40].…”
Section: In Vitro Release Studymentioning
confidence: 99%
“…The importance of the vagina as a route of drug administration comes from its rich blood supply, large surface area, high permeability to several drugs, in addition to the avoidance of the first-pass metabolism [3]. Mucoadhesion has been of great interest in the development of vaginal drug delivery systems to increase the residence time at the site of absorption [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial vaginosis (BV) is considered to be a major cause of vaginal discharge in females of childbearing age (Kenyon et al., 2013 ). BV is a clinical disorder recognized by a change in vaginal flora away from Lactobacillus species; which normally produce the lactic acid and hydrogen peroxide that maintain the acidic pH; toward various bacterial species, including different anaerobes such as Peptostreptococcus sp., Gardnerella vaginalis , Mycoplasma hominis , Staphylococcus sp., and the Enterobacteriaceae (Pandey et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%